Legal institutions : the development of dispute settlement - Stein, Peter (London: Butterworths, 1984)
The book deals with 'external 'institutions of the law:forms of dispute settlement and types of procedure and their relationship to forms of the law itself
Includes index
obn 24/01/2019
Loans
Keywords: Comparative law; Law-History; Law-Great Britain-History